2003
DOI: 10.1002/jcb.10562
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine inhibits activation‐induced T cell expression of CD2 and CD28 co‐stimulatory molecules: Role of interleukin‐2 and cyclic AMP signaling pathways

Abstract: Adenosine is an immunosuppressive molecule that is associated with the microenvironment of solid tumors. Mouse T cells activated with anti-CD3 antibody in the presence of adenosine with or without coformycin (to prevent adenosine breakdown by adenosine deaminase) exhibited decreased tyrosine phosphorylation of some intracellular proteins and were inhibited in their ability to proliferate and synthesize interleukin (IL)-2. In addition, adenosine interfered with activation-induced expression of the co-stimulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 47 publications
0
35
0
1
Order By: Relevance
“…It has been reported that hypoxia stimulates in tumor cells the release of immunosuppressive molecules (8)(9)(10), and more recently, that it increases lung cancer cell resistance to cytotoxic T-cell-mediated lysis (11). Other studies have focused on assessing the direct effect of hypoxia on the activity of innate immune effectors rather than on hypoxia-induced adaptations of tumor cells that might endow them with resistance to immunosurveillance (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that hypoxia stimulates in tumor cells the release of immunosuppressive molecules (8)(9)(10), and more recently, that it increases lung cancer cell resistance to cytotoxic T-cell-mediated lysis (11). Other studies have focused on assessing the direct effect of hypoxia on the activity of innate immune effectors rather than on hypoxia-induced adaptations of tumor cells that might endow them with resistance to immunosurveillance (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…The low potency of the agonist in the stimulation of Ca 2ϩ increase indicates that Cl-IB-MECA elevated calcium by an unknown mechanism that cannot clearly be related to A 3 receptor activation (data not shown). However, there are other effector systems that may be activated by A 3 subtypes to modulate immune functions (Butler et al, 2003), and ongoing studies in our labora- tory are aimed at evaluating the A 3 receptor involvement in cytokine release and its role in the expression of T cells activation markers.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleoside interferes with activation-induced expression of the costimulatory molecules CD2 and CD28, possibly through A 3 AR recruitment (Butler et al, 2003). However, the adenosine-mediated inhibitory effect on the ability of lymphokine-activated killer cells to kill tumor cells has essentially been attributed to the cAMPelevating A 2A AR (Raskovalova et al, 2005).…”
Section: Immune System and Inflammationmentioning
confidence: 99%